ВЫСОКИЕ ЭКГ АМПЛИТУДЫ КАК ПРЕДИКТОРЫ РАЗВИТИЯ ГИПЕРТРОФИЧЕСКОЙ КАРДИОМИОПАТИИ У ДЕТЕЙ - Голубина, Ирина Вячеславовна; Хакимов, Джасур Пулатович; Сафаров, Зафар Файзуллаевич; Кариева, Шахноза Абдукамаловна (Медицина: теория и практика, 2020)